The Impact of Soliloquy Approaches on Digital EFL Speaking Skill Instruction - Hengki Hengki; Ratna Ratna; Ahmad Al Yakin (Journal of English Education and Teaching, 2023)
This research investigates the requirement for soliloquies to be performed for the aim of developing speaking abilities using modifications of soliloquy performers whose exceptional performances have been shown. in Hamlet's famous play. This discovery calls into question the views of some critics who believe that soliloquy is irrelevant, confusing, and unneeded in the context of the play. This study highlights numerous critical points to achieve two crucial goals: practicing acting and practicing speaking English, both of which are connected. They have expressed themselves in public by listening to their conscience when unhappy and crying, when angry and shouting words accompanied by screams of irritation, and when joyful, happy, and grateful to God for the wonderful accomplishment they have achieved. Flat, low, and high notes, as well as sorrowful and glad sounds, are all played. Embody eloquence. They were aware that they were in the presence of many eyes and cameras, so they did not turn their backs on them. Dialog, characters, and facial expressions are all included. The use of words when expressing oneself through the gaze. These critical features were preserved, resulting in an outstanding performance. Their degree of performance is incredibly fulfilling; study data demonstrate that posttest scores considerably outnumber pretest scores.  Drama activities are related to speaking or oral communication. The connection between oral communication and theater is intended to bridge the gap between the classroom and the outer world. Drama activities might help to enliven and improve speaking skills.